Morphological description and DNA barcoding research of nine Syringa species - Zhang, Meiqi; Zhai, Xiaoou; He, Lianqing; Wang, Zhen; Cao, Huiyan; Wang, Panpan; Ren, Weichao; Ma, Wei (Frontiers in Genetics, 2025)
IntroductionSyringa plants are highly valued for their ornamental qualities. However, traditional morphological identification methods are inefficient for discriminating Syringa species. DNA barcoding has emerged as a powerful alternative for species identification, but research on Syringa DNA barcodes is still limited.MethodsThis study employed a multi-locus strategy, combining the nuclear ITS2 region with chloroplast genome regions psbA-trnH, trnL-trnF, and trnL to evaluate the effectiveness of Syringa DNA barcodes. The assessment involved genetic distance analysis, BLAST searches in NCBI, sequence character analysis, and phylogenetic tree construction, examining both individual and combined sequences.ResultsThe genetic distance analysis showed that the sequence combination of ITS2 + psbA-trnH + trnL-trnF exhibited a variation pattern where most interspecific genetic distances were greater than intraspecific genetic distances. The Wilcoxon signed-rank test results indicated that, except for psbA-trnH, the interspecific differences of the ITS2 + psbA-trnH + trnL-trnF sequence were greater than those of all single and combined sequences. BLAST analysis revealed that the identification rate for nine Syringa species using ITS2 + psbA-trnH + trnL-trnF could reach 98.97%. The trait-based method also demonstrated that ITS2 + psbA-trnH + trnL-trnF could effectively identify the nine Syringa species. Furthermore, the neighbor-joining (NJ) tree based on ITS2 + psbA-trnH + trnL-trnF clustered each of the nine Syringa species into distinct clades.DiscussionThe study ultimately selected the barcode ITS2 + psbA-trnH + trnL-trnF, with an identification rate of 93.6%, as the optimal barcode for identifying nine species of Syringa trees. This combination proved to be highly effective in discriminating Syringa species, highlighting the potential of DNA barcoding as a reliable tool for species identification in Syringa. Future research could focus on expanding the sample size and exploring additional genetic markers to further enhance the accuracy and applicability of DNA barcoding in Syringa species identification.